XPS-MoSCoW: A Prioritization-Based Hybrid Agile Model of SCRUM and Extreme Programming - Thirugnanam, Mythili; Mohan, Prajval; Narayan, Pranav; Sarkar, Supratim (International journal of software innovation, 2022)
This paper presents a thorough analysis of the existing SCRUM model and the Extreme programming model for software testing and deployment and proposes a new hybrid model for software development. On reviewing the various static agile models, we concluded that the development process of the SCRUM model focused on the management aspect of software testing and deployment. In the case of Extreme programming, the engineering practices are applied to the project itself. No model effectively focuses on balancing management as well as the engineering practices of the software deployment cycle. In this paper, we have proposed an improved model called the XPS-MoSCoW Hybrid programming model that carefully integrates the features of both the SCRUM and Extreme programming models. The tasks executed using our hybrid model are prioritized using the MoSCoW prioritization rules, in which tasks with higher priorities enter first into the sprint backlog. Looking at the implementational results of this model when deployed in a startup, it is eminent how our hybrid model surpasses these static models.